Quantitative proteomics and applications in covalent ligand discovery - Basu, Ananya A.; Zhang, Xiaoyu (Frontiers in Chemical Biology, 2024)
The development of multiplexing technologies for proteomics has enabled the quantification of proteins on a global scale across samples with high confidence. In the covalent ligand discovery pipeline, quantitative proteomics can be used to establish selectivity profiles and provide critical mechanistic insight into the action of lead compounds. Current multiplexing systems allow for the analysis of up to eighteen samples in a single run, allowing proteomic analyses to match the pace of high-throughput covalent ligand discovery workflows. This review discusses several quantitative proteomic techniques and their applications in the field of covalent ligand discovery.